IMPROVING THE IMAGE OF A BANANA USING THE OPENING AND CLOSING METHOD - Fauziah, Siti; Merlina, Nita; Mayangky, Nissa Almira; Hasan, Muhamad; Fahrurrozi4, Nabil Ali; Panjaitan, Yogi Yosua; Putra, Ananta Kusuma (LPPM Universitas Nusa Mandiri, 2025)
One significant technique in image processing is morphological image operations, which include methods such as opening and closing. This research explores the application of the opening and closing methods in improving the quality of banana images. The Opening process effectively reduces noise and eliminates small, unwanted details, improving the clarity of the image. However, the Closing process presents some challenges, particularly in altering the natural texture of the banana and blurring fine lines. Careful adjustments are necessary to avoid reducing the visual quality of the image. The study begins with pre-processing steps such as image cleaning and contrast adjustment to enhance the image clarity. The Opening operation, using mathematical morphology and a structural element, removes unwanted small elements from the image, making fine lines and textures more visible for further analysis. The Closing operation, applied after Opening, fills small gaps and connects separated parts of the banana image, restoring the original structure and maintaining image continuity. The combined application of opening and closing methods significantly enhances the quality of banana images by improving clarity, preserving structural integrity, and optimizing overall visual appearance.